Strategi Pengembangan Kecerdasan Emosional Pada Anak Usia Dini Melalui Aktivitas Bermain - Fadhila, Luthfia Rizka; Khadijah, Khadijah; Maghfirah, Maghfirah; Aulia, Sarah Rizky; Salsabilah, Salsabilah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study discusses the strategy of developing social-emotional intelligence in early childhood through play activities, focusing on the experience at PAUD Bunda Isnaini. Through interviews with Mrs. Mayani, a teacher at the PAUD, and direct observations of teaching practices, this study explores the effectiveness of these strategies, the most appropriate age, and the challenges faced in their implementation. The results indicate that play activities such as collaborative games, role-playing, and sharing games are effective in developing social-emotional skills in early childhood. However, time and space constraints for play and the diverse personal needs of children remain challenges that need to be addressed. In conclusion, play activities are a potential means to achieve the goals of social-emotional development in early childhood.